Синтез и характеризация керамики BaxMg(2 – x)F4, активированной вольфрамом; Физика и химия стекла; Т. 49, № 3 - Лисицын В. М. Виктор Михайлович; Мусаханов Д. А. Досымхан Абитханович; Коржнева Т. Г. Татьяна Геннадьевна; Стрелкова А. В. Асель Викторовна; Лисицына Л. А. Людмила Александровна; Голковский М. Г. Михаил Гедалиевич; Жунусбеков А. М. Амангелды Магмурович; Карипбаев Ж. Жакып; Козловский А. Л. Артем Леонидович (2023, 2023)
Заглавие с экрана